PhET Simulation Effectiveness as Laboratory Practices Learning Media to Improve Students’ Concept Understanding - Inayah, Nailil; Masruroh, Masruroh (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
PhET Simulation could be an alternative learning media for subject which is need laboratory practices that could not be adapted well in distance learning during pandemic of Covid-19. This study attempts to describe the effectiveness of PhET Simulation as learning media for laboratory practices during pandemic. This research is pre experimental research using pre-test post-test design with 30 students as sample that was taken using saturated sampling technique. The effectiveness of PhET simulation is seen from student’s concept understanding, and student’s response. The instruments used in this study was students’ understanding concept test sheet and responses questionnaire. The effectiveness analysis of PhET Simulation that is integrated in distance learning was done by analyzing students’ pretest and post-test scores by using paired-sample t-test, n-gain score average, and students’ responses.  The results showed that there is significant increase of students’ concept understanding at α = 5%, the average N-gain of students concept understanding was 0.63 (medium), and also the implementation of PhET simulation achieved very positive responses. Overall, it can be concluded that the PhET simulation is effective as a learning media for laboratory practices during pandemic to improve students’ concept understanding.